Kepastian Hukum Proses Pendaftaran Peralihan Hak Atas Tanah Yang Diperoleh Melalui Jual Beli : (Studi Di Kantor Pertanahan Lombok Timur) - Ricki Ardian Prasaja; Arba Arba (Fakultas Hukum Universitas Mataram, 2022)
This study describes the process of land ownership transfer application obtained from purchasing. It focuses on the time period from purchasing to application submission according to Article 103 Paragraph (1) and (7) of the Regulation of Ministry of Agrarian No 3 of 1997. This study is a normative-empirical one, with statute, conceptual, and sociological approaches. Results of this study show that according to the Regulation, application submission is no later than 7 days after purchasing. In the other word, it neglects Paragraph (7) that allows application submission exceeding 7 days. The Agrarian Office does not proceed application that is submitted more than 7 days. In the case it exceeds 7 days, applicant is to renew and adjust the deeds and its date.